THE INTERFACE BETWEEN LIFE SKILLS AND CAREER EDUCATION: THE ASPECT OF SECONDARY EDUCATION - Gudžinskienė, Vida; Railienė, Asta (Acta Paedagogica Vilnensia, 2012)
One of the key objectives of the Lithuanian education system is to help the individuals and society to respond to the current major challenges and to facilitate the use of multiple opportunities. In a knowledge society, everybody should be equipped with the knowledge how to adapt to market changes and choose a professional career matching individual and public needs. Educational institutions are implementing the programmes for the development of everyday life skills. The aim of these programmes is to help learners find their place in society, behave positively and manage everyday life needs and problems. Career competences are a system of knowledge, skills and attitudes which serve as the basis for the enhancement of self-cognition and career opportunities of an individual, including career development and career realisation (in coordination with other spheres of life). The development of career competences and life skills is not possible without the involvement of relevant institutions: family, general education schools, and non-formal education institutions.The object of the study was the interface between the development of life skills and career competences. The aim was to reveal this interface in the context of secondary education. The analysis of the interface between life skills and career education vas based on the theoretical principles of investigating educational reality and the theory of education levels. The article summarizes that there are created legal presumptions for developing life skills and career competences in Lithuania. Life skills and career education are an integral part of the curriculum, which depend on the educational environment, educational standards, educators. The education of life skills directly interacts with the development of career competences: certain life skills lead to some career competences.
Keywords: life skills; career competences; career education; secondary education